Role of Cytokines in Experimental and Human Visceral Leishmaniasis - Samant, Mukesh; Sahu, Utkarsha; Pandey, Satish Chandra; Khare, Prashant (Frontiers in Cellular and Infection Microbiology, 2021)
Visceral Leishmaniasis (VL) is the most fatal form of disease leishmaniasis. To date, there are no effective prophylactic measures and therapeutics available against VL. Recently, new immunotherapy-based approaches have been established for the management of VL. Cytokines, which are predominantly produced by helper T cells (Th) and macrophages, have received great attention that could be an effective immunotherapeutic approach for the treatment of human VL. Cytokines play a key role in forming the host immune response and in managing the formation of protective and non-protective immunities during infection. Furthermore, immune response mediated through different cytokines varies from different host or animal models. Various cytokines viz. IFN-γ, IL-2, IL-12, and TNF-α play an important role during protection, while some other cytokines viz. IL-10, IL-6, IL-17, TGF-β, and others are associated with disease progression. Therefore, comprehensive knowledge of cytokine response and their interaction with various immune cells is very crucial to determine appropriate immunotherapies for VL. Here, we have discussed the role of cytokines involved in VL disease progression or host protection in different animal models and humans that will determine the clinical outcome of VL and open the path for the development of rapid and accurate diagnostic tools as well as therapeutic interventions against VL.